The Influence of Marketing Mix Components on Consumer Choices: A Study on Azka Cultivation Business - Safitri, Ratna; Abidin, Zaenal; Munip, Al; Saputra, Ahmad Edi (Zabags International Journal of Economy, 2025)
This study aims to determine the influence of the marketing mix consisting of products, prices, locations and promotions on the decision to purchase fish seeds in the Azka cultivation business in Talang Babat village. The method used in this study is explanatory research with a cantitive approach, looking at the influence of independent variables, namely: product, price, location and promotion on the bound variable, namely the purchase decision. The respondents in this study are prospective consumers in the Azka cultivation business in Talang Babat Village. The determination of the number of samples was carried out using the Purposive Sampling technique. The number of samples taken was 98 respondents. Hypothesis analysis uses multiple linear regression. The results of the study show that: First, there is no positive and significant influence between product variables on purchase decisions. Second; There was no positive and significant influence between price variables on purchase decisions. Third; There was a positive and significant influence between the place variables on the purchase decision. Fourth; There is a positive and significant influence between promotional variables on purchase decisions. Fifth; from the results of the F test, it can be known that it is 66.70%.